Effects of expansionary monetary policy shocks on financial variables - Dhankhar, Rashmi (Kansas State University, 2010)
This thesis uses a structural VAR approach with a recursiveness assumption to examine the effects of an expansionary monetary policy shock on financial variables. We build this on the established research of the effects of monetary shocks on macro variables by measuring the expansionary shock as an increase in the money supply. We also investigate interest rate policy and test whether financial market variables matter for the determination of interest rate. We analyze four different cases in this paper using the innovations in the money supply, non-borrowed reserves, the interest rate and bond yield (including bonds with remaining maturity period close to 30- years) as a measurement for the expansionary monetary policy shock.
Keywords: monetary policy shocks; financial variables; Vector Auto Regression; Economics, Finance (0508)